2023
DOI: 10.1038/s41598-022-22841-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between cannabis use and blood pressure levels according to comorbidities and socioeconomic status

Abstract: The associations between blood pressure and cannabis use remain inconsistent. The purpose of our study was to examine gender stratified associations of cannabis use and blood pressure [systolic, diastolic blood pressure (BP), pulse pressure (PP)] levels among the general UK Biobank population based study. Among 91,161 volunteers of the UK Biobank population, cannabis use status was assessed by questionnaire and range as heavy, moderate, low and never users. Associations between cannabis use and BP were estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Alcohol drinker status was determined based on participants’ responses regarding their alcohol consumption: “current,” “past,” or “never” [ 35 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol drinker status was determined based on participants’ responses regarding their alcohol consumption: “current,” “past,” or “never” [ 35 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…These categories included low users of cannabis, defined as those who reported lifetime use 1 to 2 times or 3 to 10 times, and continued users, subdivided into moderate users (11-100 times) and heavy users (>100 times). 26 Heavy cannabis use could also be defined, as in the literature, as daily or near daily use for at least a few months. 27…”
Section: Cannabis Usementioning
confidence: 99%
“…Body mass index (BMI) was calculated as weight in kilograms divided by height in meters squared and was categorized as high (>30), moderate (25)(26)(27)(28)(29)(30), or low (<25). Detailed information on biological parameters can be found in the UK Biobank protocol.…”
Section: Covariatesmentioning
confidence: 99%
“…17 However, this finding is not consistent across studies, and modest 18 or inverse associations have been reported elsewhere. 19 In a prospective study of hypertensive patients, Abuhasira et al 20 found that cannabis therapy for 3 months was associated with a reduction in 24-hours systolic and diastolic BP. A randomized, double-blind, crossover study including nine healthy male volunteers suggests that acute administration of CBD reduces resting systolic BP and stroke volume, with increased heart rate and maintained cardiac output.…”
Section: What Are the Clinical Implications?mentioning
confidence: 99%